Assembling a new vehicle: the impact on the development of processes, parts and tooling for the assembler and its suppliers (2022)
The following article shows the impact generated in RENAULT-Sofasa for the design or redesign of production processes applied to the vehicle assembly plant and its local suppliers due to the development of a new vehicle focused on the Latin American market, allowing the consolidation of a product and process innovation. The vehicle´s design seeks to meet the safety and quality requirements demanded by end users. Therefore, the production processes in the assembly plant and the parts suppliers had to be transformed. The methodological section describes the incorporation of robots and process automation to optimize the assembly, ensure quality, and improve the security and ergonomic conditions for employees of the assembly factory, among other features that significantly modified the production process in the plant. In the case of parts suppliers, RENAULT-Sofasa provided support processes, technology transfer, and direct advice. Thus, it secured the acquisition of capabilities that would guarantee the quality of parts for the new vehicle. The results obtained showed that the development of parts with local suppliers and the new processes in the assembly line are effective in producing a vehicle of high quality. The article contributes to the Colombian engineering community about its own developments that have been completed in the country and the possibility of contributing to the automotive industry.